The solution to the equation 57 - 6 2 ÷ (2 + 1) · 4 is -25.7.
An equation is an expression used to show the relationship between two or more numbers and variables.
Given the equation:
57 - 6 2 ÷ (2 + 1) · 4
To solve the equation, use BODMAS, first deal with the bracket"
= 57 - 62 ÷ (3).4
Second, solve the division:
= 57 - 20.7 . 4
Next deal with the multiplication:
= 57 - 82.7
Next deal with the subtraction:
= -25.7
The solution to the equation 57 - 6 2 ÷ (2 + 1) · 4 is -25.7.
Find out more on equation at: https://brainly.com/question/2972832